2009
DOI: 10.1073/pnas.0810169106
|View full text |Cite
|
Sign up to set email alerts
|

Donor Toll-like receptor 4 contributes to ischemia and reperfusion injury following human kidney transplantation

Abstract: While studies in animal models have linked Toll-like receptor (TLR) 4 signaling to kidney injury induced by ischemia and reperfusion, the relevance of TLR4 activation to allograft injury in human kidney transplants is unknown. Here we show that TLR4 is constitutively expressed within all donor kidneys but is significantly higher in deceased-, compared with living-donor organs. Tubules from deceased-but not living-donor kidneys also stained positively for high-mobility group box-1 (HMGB1), a known endogenous TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
242
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(261 citation statements)
references
References 45 publications
(52 reference statements)
14
242
0
4
Order By: Relevance
“…TLR4 signalling also plays an important role in the development of various kidney diseases, yet the role of TLR4 in diabetic glomerulopathy or hyperlipidaemiainduced kidney damage remains to be elucidated [8][9][10][11][12][13]. Recently, Burkhardt et al and Bouma et al reported that serum S100A8/A9 complex concentrations were elevated in patients with diabetes [33,34].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TLR4 signalling also plays an important role in the development of various kidney diseases, yet the role of TLR4 in diabetic glomerulopathy or hyperlipidaemiainduced kidney damage remains to be elucidated [8][9][10][11][12][13]. Recently, Burkhardt et al and Bouma et al reported that serum S100A8/A9 complex concentrations were elevated in patients with diabetes [33,34].…”
Section: Discussionmentioning
confidence: 97%
“…TLR4, one of the best-characterised TLRs, binds with lipopolysaccharide from Gram-negative bacterial cell walls and with several endogenous ligands [7]. TLR4 also plays an important role in various kidney disorders, such as glomerulonephritis, renal ischaemia and diabetic tubular inflammation [8][9][10][11][12][13], but the role of TLR4 in diabetic glomerular injury and hyperlipidaemia-induced kidney damage remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, белки теплового шока 60,70 и gp 96, также как и HMGB1, были причастны к сигнализации об опасности через TLRs [46][47][48][49]. Сигналы TLRs активны во время некоторых условий воспаления, лишённых патогена, таких, которые наблюдаются при повреждении типа ишемии-реперфузии, ассоциированном с трансплантационной хирургией [50][51][52][53][54]. Это предполагает возникновение эндогенных лигандов в результате самой процедуры трансплантации, которые могут, подобно лигандам, происходящим от микробов, активизировать врожденные иммунные клетки, которые могут затем способствовать отторжению через адаптивную иммунную систему [5,12].…”
Section: повреждение и эндогенные стрессовые факторы при трансплантацииunclassified
“…Furthermore, ischaemia-reperfusion injury leads to cellular death and release of immunologically active molecules called damage-activates molecular patterns (DAMPs) such as heatshock proteins, adenosine triphosphate (ATP), uric acid, ribonucleic acid (RNA), deoxyribonucleic acid (DNA), as well as proteins derived from extracellular matrix including hyaluronan fragments and heparin sulphate proteoglycans [29,30]. Epithelial, mesenchymal and endothelial cells within the donor kidney express receptors for which include toll-like receptors (TLRs) and nucleotide-binding oligomerization domain-like receptors (NLRs), Interaction of the products of cellular injury with TLR and NLR sets of production of cytokines and chemokines, which are strong attractants for recipient innate immune cells [31][32][33][34].…”
Section: Allorecognition and T Cell Activationmentioning
confidence: 99%